2014
DOI: 10.1002/cne.23694
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory ensheathing cells are the main phagocytic cells that remove axon debris during early development of the olfactory system

Abstract: During development of the primary olfactory system, axon targeting is inaccurate and axons inappropriately project within the target layer or overproject into the deeper layers of the olfactory bulb. As a consequence there is considerable apoptosis of primary olfactory neurons during embryonic and postnatal development and axons of the degraded neurons need to be removed. Olfactory ensheathing cells (OECs) are the glia of the primary olfactory nerve and are known to phagocytose axon debris in the adult and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
83
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 43 publications
1
83
2
Order By: Relevance
“…We have previously generated a transgenic reporter line of mice, OMPZsGreen, in which olfactory sensory neurons of the main and accessory olfactory systems express ZsGreen fluorescent protein (Ekberg et al, 2011). In these mice, cell debris arising from olfactory axons retains expression of ZsGreen which is then able to be detected in radial glia that phagocytose the debris during development (Amaya et al, 2015) and in main olfactory OECs in the embryo (Nazareth et al, 2015). In order to determine the phagocytic capabilities of OECs of the accessory olfactory system, we have now examined the accessory olfactory nerve of OMP-ZsGreen mice and compared them to OECs of the main olfactory system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously generated a transgenic reporter line of mice, OMPZsGreen, in which olfactory sensory neurons of the main and accessory olfactory systems express ZsGreen fluorescent protein (Ekberg et al, 2011). In these mice, cell debris arising from olfactory axons retains expression of ZsGreen which is then able to be detected in radial glia that phagocytose the debris during development (Amaya et al, 2015) and in main olfactory OECs in the embryo (Nazareth et al, 2015). In order to determine the phagocytic capabilities of OECs of the accessory olfactory system, we have now examined the accessory olfactory nerve of OMP-ZsGreen mice and compared them to OECs of the main olfactory system.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the continual turnover of olfactory sensory neurons, there is a constant need for removal of the debris arising from degraded axons. Studies have shown that OECs, rather than macrophages, are the main phagocytic cells responsible for the removal of cellular debris throughout development (Nazareth et al, 2015), in the adult (Su et al, 2013) and after injury (Nazareth et al, 2015;Wewetzer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that olfactory glia, olfactory ensheathing cells (OECs), play an essential role in preventing microbial invasion of the olfactory nerve by phagocytosing microorganisms (2,3). The glia of the trigeminal nerve are Schwann cells, which are also phagocytic and remove debris after peripheral nerve injury as well as at least some types of bacteria (3,4).…”
mentioning
confidence: 99%
“…We previously demonstrated that B. pseudomallei rapidly colonizes the OM and brain in the absence of detectable blood colonization (27), and B. pseudomallei rapidly penetrates the olfactory and trigeminal nerves to infect the central nervous system (28). In the primary olfactory nerve, OECs are the principal phagocytic cells and macrophages are largely excluded even after injury (53). OECs can phagocytose bacteria in vitro (54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…KC and G-CSF are both potent chemoattractants and activators of neutrophils (73,74), whereas MCP-1 specifically attracts macrophages and memory T cells (75). Whether the upregulation of cytokines and chemokines by OECs acts to recruit leukocytes in the olfactory nerves is uncertain, as previous studies have shown that cells of the immune system are largely excluded from the olfactory nerve and that OECs perform the role of innate immune cells instead (53,76).…”
Section: Discussionmentioning
confidence: 99%